2001
DOI: 10.1002/1521-3927(20010301)22:5<281::aid-marc281>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Molecular, Nanostructural and Mechanical Characteristics of Lamellar Triblock Copolymer Blends: Effects of Molecular Weight and Constraint

Abstract: While theoretical and experimental efforts have thoroughly addressed microphase‐ordered AB diblock copolymer blends with a parent homopolymer (hA or hB) or a second block copolymer, surprisingly few studies have considered comparable ABA triblock copolymers in the presence of hB or an AB diblock copolymer. In this study, we elucidate the roles of additive molecular weight and constraint by examining three matched series of miscible ABA/hB and ABA/AB blends. Self‐consistent field theory is employed to analyze m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
46
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 36 publications
4
46
0
Order By: Relevance
“…molecular architecture enables network formation and imparts valuable macroscopic properties. Independent experimental 19,20 and theoretical [21][22][23] investigations have long sought to correlate the fraction of midblock bridging with bulk mechanical properties in molecularly symmetric copolymers (with A-endblocks of equal repeat unit number, N A ) in the melt, as well as in the presence of a selective solvent. 24 In this case, each copolymer molecule can be classified as either a bridge (each endblock resides in a different microdomain), a loop (both endblocks locate within the same microdomain), a dangle (one endblock sits in a microdomain while the other remains in the matrix), or mixed (both endblocks are unsegregated and stay within the matrix).…”
mentioning
confidence: 99%
“…molecular architecture enables network formation and imparts valuable macroscopic properties. Independent experimental 19,20 and theoretical [21][22][23] investigations have long sought to correlate the fraction of midblock bridging with bulk mechanical properties in molecularly symmetric copolymers (with A-endblocks of equal repeat unit number, N A ) in the melt, as well as in the presence of a selective solvent. 24 In this case, each copolymer molecule can be classified as either a bridge (each endblock resides in a different microdomain), a loop (both endblocks locate within the same microdomain), a dangle (one endblock sits in a microdomain while the other remains in the matrix), or mixed (both endblocks are unsegregated and stay within the matrix).…”
mentioning
confidence: 99%
“…SAXS analysis of SIS/SI blends has shown an increase in the average spacing between PS domains with increasing SI fraction, supporting this argument. 8 This behavior is also similar to that of copolymer/ homopolymer blends. 9 The addition of AB diblock, and subsequent decrease in bridging, leads to a decrease in the storage modulus (E′) of the ABA triblock blend.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of diblock content on E′ becomes less pronounced above 20% diblock content by weight. 8 Even though the number of free ends of B-chains increase with increasing diblock content, at high enough concentrations it is possible for the chains to form entanglements resulting in a smaller decrease in E′. Lovisi et al 10 also reported a decrease in the elastic response of a styrene−butadiene−styrene (SBS) copolymer containing various amounts of uncoupled butadiene chains.…”
Section: Introductionmentioning
confidence: 99%
“…The primary reason for these differences is that the third block may locate in either the same microdomain as the first so that the B midblock forms a loop or a different microdomain so that the midblock forms a bridge. Several experimental [18,19] and theoretical [16,20,21] studies have examined the consequences of midblock bridging (and network formation) in ABA triblock copolymer systems, but nearly all these previous efforts have focused on molecularly (albeit not necessarily compositionally) symmetric copolymers wherein the two A end blocks are of identical length. Such limited assessment reflects the commercial relevance of molecularly symmetric triblock copolymers, particularly as thermoplastic elastomers [22].…”
mentioning
confidence: 99%